Medición del Good Will aplicando NIC 38, caso farmacéutica Buena Salud S.A. - Calvache Blacio, Allison Alexandra (Universidad Técnica de Machala, 2022)
The effects of economic change, resulting from globalization, have led companies, regardless of the activity they perform, to adapt to the new regulations established for the accounting field, in order to achieve financial and accounting efficiency, as well as business prestige. That is why, in addition to seeking to obtain monetary resources, companies must ensure that a solid and stable image of the entity is projected. In the case of the pharmaceutical sector, due to the wide variety of services it generates, together with the constant growth of patents, production rights and trademarks, licenses, among others, it becomes an ideal pattern for the generation of intangible assets. Intangible assets are distinguished by being imperceptible to the eye, characterized by their immaterial nature, and constituting a key element for the generation of value in the market that a company has. This research work seeks to determine the good will of the pharmaceutical company "Buena Salud S.A.", by means of the provisions of IAS 38, in order to carry out a practical execution within the professional field. A descriptive research is established, with the use of the analytical method and based on scientific documents taken from various databases that enjoy academic prestige. Subsequently, a practical exercise is presented in which the measurement and accounting recording of an intangible asset is established in accordance with the provisions of IAS 8, and finally, the conclusions drawn from the research are shown.
Los efectos de cambio económico, consecuentes de la globalización, han llevado a que las empresas, indistintamente de la actividad que desempeñen se adapten a las nuevas normativas instauradas para el campo contable, a fin de alcanzar la eficiencia financiera y contable, además del prestigio empresarial. Es por ello que, las empresas además de buscar la obtención de recursos monetarios, deben procurar que se proyecte una imagen sólida y estable de la entidad, en el caso del sector farmacéutico, debido a la gran variedad de servicios que genera, aunado al crecimiento constante de patentes, derechos y marcas de producción, licencias, entre otros, se convierte en un patrón ideal para la generación de activos intangibles. Los activos intangibles se distinguen por ser imperceptibles a la vista, caracterizados por su naturaleza inmaterial, y constituyéndose como un elemento clave para la generación de valor en el mercado que tiene una empresa. El presente trabajo de investigación busca determinar el good will de la empresa farmacéutica “Buena Salud S.A”, mediante lo que establece la NIC 38, a fin de una ejecución práctica dentro del campo profesional. Se establece una investigación descriptiva, con el uso del método analítico y fundamentado con documentos científicos tomados de diversas bases de datos que gozan de prestigio académico. Posteriormente se expone un ejercicio práctico en donde se establece la medición y registro contable de un activo intangible conforme lo dispuesto en la NIC 8, finalmente se muestran las conclusiones producto de la investigación.
Keywords: GOODWILL; ACTIVOS INTANGIBLES; MEDICIÓN; AMORTIZACIÓN